Active Control of Asymmetric Fano Resonances with Graphene–Silicon‐Integrated Terahertz Metamaterials. Issue 2 (8th January 2020) - Li, Quan; Gupta, Manoj; Zhang, Xueqian; Wang, Shuang; Chen, Tai; Singh, Ranjan; Han, Jiaguang; Zhang, Weili
Abstract: Planar metamaterials are extensively studied in recent years due to their potential applications in design of flat optical components, ultrasensitive sensors, lasing spasers, and nonlinear devices. Recent studies have reported dynamic control of photoactive material–based metamaterials through optical excitation. However, most of the previous demonstrations rely on single stimulus control and typically require large fluence and ultrafast pulses of light. Here, graphene is integrated with Fano resonant metasurface on silicon substrate that provides active modulation of terahertz waves with low‐power, continuous wave (CW) optical (λ = 532 nm) excitation. More importantly, the hybrid graphene–silicon system provides "dual control" through a combination of applied electrical bias voltage and photodoping of silicon by CW illumination which alters the conductivity of the graphene resulting in an active modulation of the metamaterial resonance. Large real‐time tunability with dual control characteristics of resonant metasurfaces can be a promising route for designing active and functional terahertz metadevices. Abstract : An active terahertz Fano metadevice based on graphene–silicon hybrid system is experimentally demonstrated through application of simultaneous continuous wave (CW) optical pump and bias voltage, where the modulation is induced by the strong interaction between the graphene, the photoexcited silicon, and the metasurface resonators. The proof‐of‐concept demonstration provides a novel route for designing active terahertz modulators.